Pengaruh Literasi Digital dan Motivasi Belajar Terhadap Hasil Belajar Siswa - Dewi, Laura Etika; Syofyan, Rita; Putra, Defriko Gusma (Universitas Negeri Padang, 2024)
This research set out to answer the following questions: 1) the relationship between students' digital literacy and their desire to learn and their final grades, 2) the precise impact that digital literacy has on the academic achievement of these pupils, and 3) the precise impact that learning motivation has on the academic achievement of the candidates. A causal associative design and quantitative approach were employed to carry out the investigation in this study. The 117 students making up the XI social studies class at SMA Pertiwi 1 Padang served as the study's population. We used a proportionate random selection technique to pick 91 people to take part in the survey. The multiple linear regression analysis was conducted using SPSS version 25 software. According to the results: 1) The academic performance of students in the eleventh grade at SMA Pertiwi 1 Padang is significantly affected by their level of digital literacy as well as their enthusiasm to learn. 2) These students' digital literacy greatly enhances their academic achievement, and 3) Their level of motivation to learn has a positive and substantial effect on their academic performance. According to the report, a whopping 47.7 percent of the learning outcomes of IPS SMA Pertiwi 1 Padang class XI students are impact by digital literacy and learning motivation.